2007
DOI: 10.1063/1.2715442
|View full text |Cite
|
Sign up to set email alerts
|

Planar Hall effect and magnetic anisotropy in epitaxially strained chromium dioxide thin films

Abstract: We have measured the in-plane anisotropic magnetoresistance of 100 nm thick CrO 2 thin films at liquid He temperatures. In low magnetic fields H, both the longitudinal and the transverse ͑planar Hall͒ resistance show abrupt switches, which characteristically depend on the orientation of H. All the experimental findings consistently demonstrate that the magnetic anisotropy in these CrO 2 thin films is biaxial. We show that the biaxial magnetic anisotropy is due to epitaxial coherency strain, and that it natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…The only report in the literature on PHE measurements for CrO 2 films showed that at intermediate thickness (100 nm), films can develop biaxial magnetic anisotropy in which two magnetic easy axes occur, one in between the c and the b axes, and one mirrored around the c axis to lie in between the c and the b axes. 16 Moreover, they also predict that their films are in a single magnetic domain structure. We also probed PHE using the L structure of a 100-nm-thick film at 4.2 K in the shielded cryostat with a magnetic field applied in a parallel configuration (H I ) but our film was exhibiting uniaxial magnetic anisotropy, for details see Ref.…”
Section: Planar Hall Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The only report in the literature on PHE measurements for CrO 2 films showed that at intermediate thickness (100 nm), films can develop biaxial magnetic anisotropy in which two magnetic easy axes occur, one in between the c and the b axes, and one mirrored around the c axis to lie in between the c and the b axes. 16 Moreover, they also predict that their films are in a single magnetic domain structure. We also probed PHE using the L structure of a 100-nm-thick film at 4.2 K in the shielded cryostat with a magnetic field applied in a parallel configuration (H I ) but our film was exhibiting uniaxial magnetic anisotropy, for details see Ref.…”
Section: Planar Hall Effectmentioning
confidence: 99%
“…New in our MR data is the strongly nonmonotonous behavior around the crossover temperature of 100 K. We also study the low-field magnetoresistance behavior and come to a similar conclusion as König et al, that intergrain tunneling magnetoresistance (ITMR) takes over from anomalous magnetoresistance (AMR) when the temperature decreases to below 100 K. 15 Data on the planar Hall effect (PHE) confirm that the magnetization does not switch in single-domain fashion in these films, different from one particular case reported by Gönnenwein. 16 The article consists of two parts. First, the measurements of the temperature-dependent resistance R(T ) of the high-field MR and of the Hall effect are presented and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…1b. In the case of TiO 2 , it was due to the peculiar circumstance that strain relaxation in the film can lead to a change in the easy-axis direction, with biaxial behavior occurring around a film thickness of 100 nm [16]. Apart from the experiments we report here, we have grown a number of films on TiO 2 , and we find that growth conditions (including substrate cleaning prior to the growth) crucially determine whether biaxial behavior occurs.…”
mentioning
confidence: 89%
“…In this paper, we report the observation of a new type of uniaxial anisotropy, associated with the in-plane crystallographic direction in the Fe film. To investigate magnetic anisotropy of the Fe film, we make use of the planar Hall effect (PHE), which arises from the tensor character of the anisotropic magnetoresistance 26 27 . Detection of this uniaxial anisotropy is possible due to the fact that in PHE measurements even very small contributions of a uniaxial anisotropy to the reorientation of magnetization between magnetic easy axes lead to conspicuous asymmetric behavior of the hysteresis loops observed by planar Hall resistance (PHR), as discussed below.…”
mentioning
confidence: 99%